The Protein Profiles of Trichophyton rubrum by SDS-PAGE - M Mahmoudi Rad; F Zaini; M Pezeshki; P Kordbacheh; E Elmi Akhouni; M Emami (Tehran University of Medical Sciences, 2001)
In the present study, we investigated total cell protein patterns of ten isolates of Trichophyton rubrum by SDS-PAGE on 12.5% polyacrylamide resolving gels. Twenty-two protein bands were detected with molecular weights in the range of 23.2 to 131.8 KD. Proteins of 23.2, 25.4, 26.7, 28.2, 30.2, 33.1, 34.7, 38,41.7, 47.9, 52.5, 56.2, 61.7, 67.6, 70.8, 75.9, 80, 84.1, 93.3, 102.3, 114.8, 131.8 were present but their frequencies varied among the isolates. Protein bands of 23.2, 38, 47.9, 52.5, 84.1 were common among the isolates and could be specific to recognize species differences. Protein analysis by SDS-PAGE could be considered a useful technique in identifying differences among the dermatophyte isolates.